2012
DOI: 10.1002/anie.201108155
|View full text |Cite
|
Sign up to set email alerts
|

Two Iron Catalysts are Better than One: A General and Convenient Reduction of Aromatic and Aliphatic Primary Amides

Abstract: It takes two: For the reduction of amides to amines iron catalysts were developed. A combination of two different iron catalysts made possible the challenging reduction of primary amides (see picture).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
73
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 192 publications
(74 citation statements)
references
References 72 publications
1
73
0
Order By: Relevance
“…Scheme 9: reduction of primary amides into amines with in situ generated iron complex [20]. combination [20].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Scheme 9: reduction of primary amides into amines with in situ generated iron complex [20]. combination [20].…”
Section: Methodsmentioning
confidence: 99%
“…Based on these previous results, the group of Beller investigated a combination of two different iron-catalyzed reactions to obtain the primary amines: one iron precursor to catalyze dehydration of amides to nitriles and a second one for the reduction step [20]. After a complete screening of the reaction parameters (iron salt pre-catalysts and loading, nature of the nitrogen-based ligands, solvent, silane), the scope was performed with 5 mol% of for the reduction of nitriles, in the presence of (EtO) 2 MeSiH (Scheme 9).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[10] Beller showed that the iron-carbonyl complex [Fe 3 -(CO) 12 ] could be used together with polymethylhydrosiloxane (PMHS) for the direct reduction of tertiary amides to amines at 100°C. [16] We recently reported that a highly active, in situ formed iron/NHC complex formed from iron(II) acetate and 1-(2-hydroxyethyl)-3-methylimidazolium triflate [HEMIM]-[OTF] efficiently catalyzed the reduction of aldehydes and ketones under hydrosilylation conditions (Scheme 1). The reaction could be carried out under both thermal and photoassisted conditions by using either PMHS or 1,1,3,3-tetramethyldisiloxane (TMDS) as the reducing agent.…”
Section: Introductionmentioning
confidence: 99%
“…8 Primary amides were also reduced using a diiron system with methyldiethoxysilane and achieved yields from 49 to 70%. 9 Beller has reported zinc-catalyzed reduction of tertiary and secondary amides. 10 Mild conditions are reported and wide functional group tolerance is achieved (eq.…”
Section: Introductionmentioning
confidence: 99%